The many inventions of the EJA - Sales, Sandra Regina; Paiva, Jane (Education Policy Analysis Archives, 2014)
Using the processes of making up people of Ian Hacking, we recount the inventions of popular education and Adult and Youth Education (EJA from the Portuguese) from the perspective of understanding who they are and how the systems of classification of subjects and subjectivities were generated. In a second step, we establish a critical dialogue between the notion of making up people with the lessons identified in the articles that make up the second special issue of EJA in EPAA, highlighting the systems of inquiry developed by the researchers-authors, their epistemologies, the methodologies of knowledge open in the field of EJA, and synthesizing what research has revealed about the many inventions of the subjects of EJA. Ultimately, we want to highlight what we, as researchers in EJA, have learnt, and what we still need to learn to effectively intervene in the multiple Latin American and Brazilian contexts towards the goal of social transformation.